Energy efficiency as a non-point source problem - Canessa, Peter, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2002)
This paper argues that improving energy efficiency in agriculture is a long-term, non-point source type of problem. "Fixing" non-point source problems generally involves changing the behavior of resource managers. These types of problems are generally addressed by programs involving three components: 1) problem awareness, 2) solution awareness, and 3) targeted resources. The concept of market transformation as applied to energy efficiency is discussed in relation to non-point source programs. Market transformation also involves changing the way end-users (managers) think and act, but also recognizes supply-side issues in terms of changing the services and hardware being offered to the end-user.
USCID/EWRI conference
Not digitized by CSUL Digital Services.
Presented at the 2002 USCID/EWRI conference, Energy, climate, environment and water - issues and opportunities for irrigation and drainage on July 9-12 in San Luis Obispo, California.